2014
DOI: 10.1556/oh.2014.29973
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nutrition therapy in patients with short bowel syndrome in line with principles of personalized medicine

Abstract: A kijelölt centrumokban gondozott rövidbél-szindrómás betegek otthoni parenteralis táplálásterápiája 2013 január-jától Magyarországon is fi nanszírozott. A szerzők a rövidbél-szindrómás betegek diagnosztikai kérdéseit, kezelését, táplálásterápiáját ismertetik a személyre szabott orvoslás elvei szerint. A rövidbél-szindróma legsúlyosabb tünetei jejunostomás betegeknél alakulnak ki, akiknek kezelését külön tárgyalják. Részletesen bemutatják az otthoni parenteralis táplálás módszerét és annak lehetséges szövődmén… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…In populations with an extreme body mass index (BMI) (BMI < 16kg/m 2 and BMI > 40 kg/m 2 ), IC was equally the first choice compared to predictive equations [ 25 ]. Several studies observed lower BMI values (16.6–21.3) in HPN patients [ 26 , 27 , 28 , 29 ]. Evaluating the accuracy of 18 predictive equations and IC for calculating REE in patients with underweight (BMI < 18.5), normal weight (18.5 < BMI < 30) and overweight (BMI > 30), all equations reached only an accuracy between 9–45% (BMI < 18.5), 12–52% (18.5 < BMI < 25), 39–58% (25 < BMI < 30) and 10–53% for BMI > 30 compared to IC [ 30 ].…”
Section: Nutritional Assessment Methodsmentioning
confidence: 99%
“…In populations with an extreme body mass index (BMI) (BMI < 16kg/m 2 and BMI > 40 kg/m 2 ), IC was equally the first choice compared to predictive equations [ 25 ]. Several studies observed lower BMI values (16.6–21.3) in HPN patients [ 26 , 27 , 28 , 29 ]. Evaluating the accuracy of 18 predictive equations and IC for calculating REE in patients with underweight (BMI < 18.5), normal weight (18.5 < BMI < 30) and overweight (BMI > 30), all equations reached only an accuracy between 9–45% (BMI < 18.5), 12–52% (18.5 < BMI < 25), 39–58% (25 < BMI < 30) and 10–53% for BMI > 30 compared to IC [ 30 ].…”
Section: Nutritional Assessment Methodsmentioning
confidence: 99%
“…Других нежелательных явлений за весь период применения ТГ не отмечено. Необходимо учитывать, что каждый больной ребенок индивидуален как по способности и срокам кишечной адаптации, так и по ответу на терапию и, соответственно, достижению и стабильности результата [31,32].…”
Section: описание клинических случаевunclassified